CHALLENGES OF DIGITAL TRANSFORMATION IN AEC INDUSTRY – BIM SPECIALISTS - Мещерякова, Ольга (SWorldJournal, 2022)
The work presents a preliminary outlines of the main roles of BIM process participants, their areas of responsibility (BIM Manager, BIM Coordinator, BIM Modeler). Gained information forms a basis for concept of choosing appropriate forms of immersing the